# Algebraic Equations MCQs with Answers

Algebraic Equations MCQs are very important test and often asked by various testing services and competitive exams around the world. Here you will find all the Important Algebraic Equations MCQs for Preparation.

The student can clear their concepts for Algebraic Equations online quiz by attempting it. Doing MCQs based Algebraic Equations will help you to check your understanding and identify areas of improvement.

## Algebraic Equations Online MCQs with Answers

What is the value of x in the equation 3x + 7 = 22?
a) 5
b) 8
c) 9
d) 15

a) 5

Solve for x: 4(x – 2) = 16 + 2x
a) -2
b) 2
c) 4
d) 8

b) 2

Simplify the expression: 2x² + 5x – 3 + x² – 2x
a) 3x² + 3x – 3
b) 3x² + 3x + 3
c) 3x² + 3x – 6
d) 3x² – 3x – 6

a) 3x² + 3x – 3

Find the value of x in the equation 5(2x + 3) = 35.
a) 1
b) 2
c) 3
d) 4

c) 3

Solve for x: 3x + 2 = 11 – 2x
a) 1
b) 2
c) 3
d) 4

b) 2

Simplify the expression: 4(x + 3) – 2(x – 5)
a) 6x + 26
b) 2x + 16
c) 2x + 26
d) 6x + 16

d) 6x + 16

Solve the equation: 2(3x – 1) = 10 – 4x
a) 1
b) 2
c) 3
d) 4

b) 2

Find the solution to the equation: 5x – 3 = 2x + 9
a) -4
b) -2
c) 4
d) 6

c) 4

Simplify the expression: 2(x – 1) + 3(2x + 5)
a) 7x + 11
b) 7x + 13
c) 5x + 11
d) 5x + 13

a) 7x + 11

Solve for x: 3(x + 2) = 9x – 6
a) -1
b) 0
c) 1
d) 2

d) 2

Find the value of x in the equation 4(x + 1) = 24.
a) 5
b) 6
c) 7
d) 8

c) 7

Solve for x: 2x – 3 = 5x + 2
a) -2
b) -1
c) 1
d) 2

a) -2

Simplify the expression: 3(x – 4) – 2(x + 2)
a) x – 14
b) x – 8
c) x – 6
d) x – 2

b) x – 8

Find the solution to the equation: 7x – 2 = 5x + 10
a) 2
b) 3
c) 4
d) 5

c) 4

Solve for x: 5 – 2(x – 3) = 3x
a) -1
b) 0
c) 1
d) 2

d) 2

Simplify the expression: 2x – (3x + 5)
a) -x – 5
b) -x + 5
c) -x – 3
d) -x + 3

a) -x – 5

Find the value of x in the equation 2(x – 3) = 10.
a) 5
b) 6
c) 7
d) 8

b) 6

Solve for x: 4x + 3 = 3(x + 1)
a) -2/7
b) -1/7
c) 1/7
d) 2/7

b) -1/7

Simplify the expression: 2(x + 1) + 3(x – 2)
a) 5x – 3
b) 5x + 3
c) 5x – 1
d) 5x + 1

a) 5x – 3

Find the solution to the equation: 4x – 5 = 2x + 9
a) -4
b) -2
c) 4
d) 6

d) 6

Solve for x: 2(3x – 1) = 10 – 4x
a) 1
b) 2
c) 3
d) 4

b) 2

Simplify the expression: 5x – (2x + 3)
a) 3x – 3
b) 3x + 3
c) 3x – 5
d) 3x + 5

a) 3x – 3

Find the value of x in the equation 3(2x + 5) = 39.
a) 4
b) 5
c) 6
d) 7

c) 6

Solve for x: 4(x – 3) = 2(x + 5)
a) -4
b) -2
c) 2
d) 4

d) 4

Simplify the expression: 3x + 4 – (2x – 5)
a) x – 1
b) x + 1
c) x – 9
d) x + 9

a) x – 1

Find the solution to the equation: 6(x + 1) = 4x + 14
a) -2
b) -1
c) 1
d) 2

b) -1

Solve for x: 2(3x – 2) = 4 – 3x
a) -1/7
b) 1/7
c) 7/9
d) 9/7

d) 9/7

Simplify the expression: 3(x + 2) – 2(x – 3)
a) 5x + 7
b) 5x + 5
c) 5x – 1
d) 5x – 7

b) 5x + 5

Find the value of x in the equation 5(2x – 1) = 39.
a) 3
b) 4
c) 5
d) 6

c) 5

Solve for x: 3(x + 2) + 2 = 2(4x – 1)
a) -7/13
b) -2/13
c) 2/13
d) 7/13

a) -7/13

Simplify the expression: 4(x + 3) – 2(2x – 5)
a) 6x + 26
b) 2x + 16
c) 2x + 26
d) 6x + 16

d) 6x + 16

Find the solution to the equation: 5x – 3 = 2x + 9
a) -4
b) -2
c) 4
d) 6

c) 4

Solve for x: 2(3x + 1) = 14 – 4x
a) 1
b) 2
c) 3
d) 4

c) 3

Simplify the expression: 2(2x – 3) + 3(x + 1)
a) 7x + 1
b) 7x – 1
c) 7x + 3
d) 7x – 3

b) 7x – 1

Find the value of x in the equation 3(2x + 1) = 27.
a) 3
b) 4
c) 5
d) 6

d) 6

Solve for x: 4(x – 1) – 3 = 5 – 2(x + 3)
a) -1/5
b) 1/5
c) 5/9
d) 9/5

b) 1/5

Simplify the expression: 3(2x + 5) – 2(3x – 1)
a) x + 13
b) x + 15
c) x – 13
d) x – 15

a) x + 13

Find the solution to the equation: 7(x + 3) = 4x + 21
a) -3
b) -2
c) 2
d) 3

d) 3

Solve for x: 5 – 3(x – 1) = 2x
a) -1/5
b) 1/5
c) 5/7
d) 7/5

d) 7/5

Simplify the expression: 2(3x + 1) – 3(x – 2)
a) 3x + 5
b) 3x – 5
c) 3x + 7
d) 3x – 7

b) 3x – 5

Find the value of x in the equation 2(4x – 1) = 15.
a) 2/3
b) 3/2
c) 7/4
d) 4/7

b) 3/2

Solve for x: 3(x + 4) = 6 – 2x
a) -2
b) -1
c) 1
d) 2

c) 1

Simplify the expression: 4(x – 3) – 2(x + 1)
a) 2x – 14
b) 2x – 10
c) 2x – 8
d) 2x – 4

a) 2x – 14

Find the solution to the equation: 3x – 5 = 2(x + 4)
a) -7
b) -6
c) 6
d) 7

c) 6

Solve for x: 5x + 3 = 4(x – 2)
a) -5
b) -4
c) 4
d) 5

d) 5

Simplify the expression: 2(x + 2) + 3(x – 1)
a) 5x + 1
b) 5x + 2
c) 5x + 3
d) 5x + 4

c) 5x + 3

Find the value of x in the equation 2(3x – 2) = 16.
a) 3
b) 4
c) 5
d) 6

c) 5

Solve for x: 4(x – 2) = 2(x + 3)
a) -2/3
b) -3/2
c) 2/3
d) 3/2

c) 2/3

Simplify the expression: 3(x + 2) – 4(x – 1)
a) -x + 5
b) -x + 1
c) -x – 5
d) -x – 1